2018
DOI: 10.1002/jso.25110
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of combination of induction chemotherapy and irreversible electroporation ablation for patients with locally advanced pancreatic adenocarcinoma

Abstract: Our study suggests that IRE is safe and effective for the control of LAPC. We surmise that the addition of IRE to a chemotherapy regimen may provide a survival advantage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 15 publications
3
24
0
Order By: Relevance
“…The median OS was 16 and 21.6 months for patients after IRE combined with chemotherapy in the SEER and SYSUCC datasets, respectively. The median OS was similar to that from a study conducted by Huang et al (26) and was significantly higher than that of patients after chemotherapy alone (8.0 months for the SEER patients and 7.1 months for the SYSUCC patients). In addition, the SEER patients had a long follow-up period, and it was shown that combination therapy was superior to chemotherapy alone with respect to not only 5-year OS rates but also 5-year CSS rates for all enrolled patients even though larger proportions of patients in the chemotherapy group received radiotherapy.…”
Section: Discussionsupporting
confidence: 83%
“…The median OS was 16 and 21.6 months for patients after IRE combined with chemotherapy in the SEER and SYSUCC datasets, respectively. The median OS was similar to that from a study conducted by Huang et al (26) and was significantly higher than that of patients after chemotherapy alone (8.0 months for the SEER patients and 7.1 months for the SYSUCC patients). In addition, the SEER patients had a long follow-up period, and it was shown that combination therapy was superior to chemotherapy alone with respect to not only 5-year OS rates but also 5-year CSS rates for all enrolled patients even though larger proportions of patients in the chemotherapy group received radiotherapy.…”
Section: Discussionsupporting
confidence: 83%
“…The safety and effectiveness of IRE have been reported by many previous studies [14, 29]. Moreover, it was illustrated that IRE was reasonably safe in LAPC after chemotherapy and with promising results regarding efficacy [17, 30]. Although it was shown that the subsequent IRE or radiotherapy after chemotherapy might result in improved survival compared with chemotherapy alone, there was no direct data illustrating the comparison of efficacy of these two local control treatments after the induction chemotherapy in patients with LAPC.…”
Section: Discussionmentioning
confidence: 91%
“…To date, increasing evidence from the literature suggests that IRE in combination with neo-adjuvant chemotherapy and/or radiotherapy elicits a survival benefit for this set of patients, confirming safety and efficacy of the procedure. 5,7,16,[48][49][50] Moreover, IRE treatment has been found to not adversely affect quality of life in the short term. 51 A recent systematic review by Moris et al provides an elaborate overview of all studies that have utilized IRE for LAPC, with a median overall survival (OS) following IRE between 7 and 27 months ( Table 2).…”
Section: Clinical Resultsmentioning
confidence: 99%